Patterns of motor signs in spinocerebellar ataxia type 3 at the start of follow-up in a reference unit. Issue 1 (December 2016) - Pulido-Valdeolivas, Irene; Gómez-Andrés, David; Sanz-Gallego, Irene; Rausell, Estrella; Arpa, Javier
Abstract Background Spinocerebellar ataxia type 3 (SCA3) is a neurodegenerative disorder that affects the cerebellar system and other subcortical regions of the brain. As for other cerebellar diseases, the severity of this type of ataxia can be assessed with the Scale for Assessment and Rating of Ataxia (SARA) which gives a total score that reflects functional impairment out of 8 cerebellar function tests. SCA3 patients score profile is heterogeneous on at the start of follow up. This study investigates possible patterns in those profiles and analyses the impact of other usually concurrent signs of impairment of extracerebellar motor systems in that profile variability by means of multivariate statistical approaches. Methods Seventeen patients with SCA3 underwent systematic anamnesis, neurological and SARA assessment, visual evaluation of123 I-Ioflupane (DaTSCAN) single-photon emission computed tomography (SPECT) imaging and electrophysiological studies (nerve conduction and electromyography). Patterns in the profiles of SARA item scores were investigated by hierarchical clustering after multivariate correspondence analysis. A network analysis was used to represent relationships between SARA item scores, clinical, genetic and neurological examination parameters as well as abnormalities of DaTSCAN SPECT imaging and electrophysiological studies. Results The most frequently altered SARA items in all patients are gait and stance, and three profiles of SCA3 patients can be distinguished depending mainly on their degree of impairment in those two items. Other SARA items like the score on heel-shin slide contribute less to the classification. Network analysis shows that SARA item scores configure a single domain that is independent of the size of the mutated expanded allele and age of onset, which are, in turn closely and inversely correlated. The severity of cerebellar dysfunction is correlated with longer disease duration, altered visual evaluation of DaTSCAN SPECT imaging and decreased patellar reflexes. Neither the presence of pyramidal or extrapyramidal signs nor the intensity of polyneuropathy is correlated with the SARA items scores. Conclusions Pattern recognition approaches are useful tools to describe clinical phenotypes of ataxias and to identify particular configurations of cerebellar signs.